Nondegenerate necessary conditions of optimality for problems without normality assumptions - F. Lobo Pereira (2006)
Nondegenerate second-order necessary conditionsof optimality for general nonlinear optimization problems arepresented and discussed in this article. Besides functionalequality and inequality constraints, we also consider constraintsin the form of an inclusion into a given closed set. Withoutassuming a priori normality, our conditions remain informativefor abnormal points, and, under very general assumptions alsotake into account the second order effect of the curvature ofthe set in the inclusion constraints.